Differences in Mid-Term Outcomes Between Patients Undergoing Thoracic Endovascular Aortic Repair for Aneurysm or Acute Aortic Syndromes: Report From the Global Registry for Endovascular Aortic Treatment. (October 2022) - Bissacco, Daniele; Domanin, Maurizio; Weaver, Fred A.; Azizzadeh, Ali; Miller, Charles C.; Gable, Dennis R.; Piffaretti, Gabriele; Lomazzi, Chiara; Trimarchi, Santi
Purpose: To analyze differences in baseline characteristics, overall mortality, device-related mortality, and re-intervention rates in patients who underwent thoracic endovascular aortic repair (TEVAR) for descending thoracic aortic aneurysm (DTAA) with atherosclerotic/degenerative cause or acute aortic syndrome (AAS), using the Global Registry For Endovascular Aortic Treatment (GREAT). Materials and Methods: Patients submitted to TEVAR for AAS or DTAA, included in GREAT, were eligible for this analysis. Primary outcome was 30-day all-cause mortality rate. Secondary outcomes were 30-day aorta-related mortality and re-intervention rate, 1-year and 3-year all-cause mortality, aorta-related mortality and re-intervention rate. Results: Five-hundred and seventy-five patients were analyzed (305 DTAA and 270 AAS). Thirty-day mortality rate was 1.3% and 1.8% for DTAA and AAS, respectively (p=0.741). One-year and 3-year mortality rates were 6.2% versus 9.3 and 17.3% versus 15.9% for DTAA and AAS, respectively (p=0.209 and p=0.655, respectively). Aorta-related mortality rates at 30 days, 1 year and 3 years were 1.3%, 1.3%, and 2.6% for DTAA, 1.8%, 4.2%, and 4.2% for AAS (p=ns). Re-intervention rates at 30 days, 1 year, and 3 years were 1.3%, 4.3%, and 7.5% for DTAA, 3.3%, 8.1%, and 10.7% for AAS (p=ns). Furthermore, a specific analysis with similar outcomes was performed dividing follow-up in 3 periods (1-30 days, 31-365 days, 366-1096 days) and describing mutual differences between 2 groups and temporal trends in each group. Conclusion: Patients who underwent TEVAR for DTAA or AAS experienced different mortality and re-intervention rates among years during mid-term follow-up. Although all-cause related deaths within 30 days were TEVAR-related, aorta-related deaths were more common for AAS patients within 1 year. A greater re-intervention rate was described for AAS patients, although only 1 year after TEVAR.